2014
DOI: 10.1016/j.ijhydene.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of highly turbulent under-expanded hydrogen and methane jets for gaseous-fuelled internal combustion engines

Abstract: Burning hydrogen in conventional internal combustion (IC) engines is associated with zero carbon-based tailpipe exhaust emissions. In order to obtain high volumetric efficiency and eliminate abnormal combustion modes such as preignition and backfire, in-cylinder direct injection (DI) of hydrogen is considered preferable for a future generation of hydrogen IC engines. However, hydrogen's low density requires high injection pressures for fast hydrogen penetration and sufficient in-cylinder mixing. Such pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 65 publications
14
64
0
Order By: Relevance
“…For instance, Ashkenas and Sherman [11], Velikorodny and Kudriakov [12] and Vuorinen et al [13] suggested C H values of 0.67, 0.63 and 0.62, respectively. The authors of the current work found that for hydrogen jets with values of NPR up to 10, C H had a value of ~0.65 [14]. An average value of C H ≈0.71 has been measured for hydrogen jets with NPR in the range 8.5-70 [14].…”
Section: Mach Disk Dimensionsmentioning
confidence: 52%
See 2 more Smart Citations
“…For instance, Ashkenas and Sherman [11], Velikorodny and Kudriakov [12] and Vuorinen et al [13] suggested C H values of 0.67, 0.63 and 0.62, respectively. The authors of the current work found that for hydrogen jets with values of NPR up to 10, C H had a value of ~0.65 [14]. An average value of C H ≈0.71 has been measured for hydrogen jets with NPR in the range 8.5-70 [14].…”
Section: Mach Disk Dimensionsmentioning
confidence: 52%
“…The authors of the current work found that for hydrogen jets with values of NPR up to 10, C H had a value of ~0.65 [14]. An average value of C H ≈0.71 has been measured for hydrogen jets with NPR in the range 8.5-70 [14]. An empirical correlation comparable to Equation (1) can also be used to estimate the Mach disk width with a respective constant C W .…”
Section: Mach Disk Dimensionsmentioning
confidence: 63%
See 1 more Smart Citation
“…see [40] for a discussion on high-speed gaseous fuel jets), causing recirculation of vapor and a widening of the vapor footprint. This effect may also have an influence on spray collapse.…”
Section: Flash-boiling Spraysmentioning
confidence: 99%
“…A parametric study has been carried out on high speed hydrogen injection, which shows the effect of grid resolution, Adaptive Mesh Refinement (AMR), and injection timing on mixture formation inside the cylinder [8]. The characteristics of hydrogen under-expanded jets has been comprehensively investigated using Large Eddy Simulation (LES) with different nozzle pressure ratios [9].…”
Section: Introductionmentioning
confidence: 99%